Molecular analysis of the genus Anoxybacillus based on sequence similarity of the genes recN, flaA, and ftsY - Colak, Dilsat Nigar; Inan, Kadriye; Karaoglu, Hakan; Canakci, Sabriye; Belduz, Ali Osman (Folia microbiologica, 2012)
Genome predictions based on selected genes would be a very welcome approach for taxonomic studies. We analyzed three genes, recN, flaA, and ftsY, for determining if these genes are useful tools for systematic analyses in the genus Anoxybacillus. The genes encoding a DNA repair and genetic recombination protein (recN), the flagellin protein (flaA), and GTPase signal docking protein (ftsY) were sequenced for ten Anoxybacillus species. The sequence comparisons revealed that recN sequence similarities range between 61% and 99% in the genus Anoxybacillus. Comparisons to other bacterial recN genes indicated that levels of similarity did not differ from the levels within genus Anoxybacillus. These data showed that recN is not a useful marker for the genus Anoxybacillus. A 550-600-bp region of the flagellin gene was amplified for all Anoxybacillus strains except for Anoxybacillus contaminans. The sequence similarity of flaA gene varies between 61% and 76%. Comparisons to other bacterial flagellin genes obtained from GenBank (Bacillus, Pectinatus, Proteus, and Vibrio) indicated that the levels of similarity were lower (3-42%). Based on these data, we concluded that the variability in this single gene makes it a particularly useful marker. Another housekeeping gene ftsY suggested to reflect the G+C (mol/mol) content of whole genome was analyzed for Anoxybacillus strains. A mean difference of 1.4% was observed between the G+C content of the gene ftsY and the G+C content of the whole genome. These results showed that the gene ftsY can be used to represent whole G+C content of the Anoxybacillus species.
Keywords: Receptors, Cytoplasmic and Nuclear; sekvence nukleotidů; Phylogeny; Molecular Sequence Data; sekvenční homologie nukleových kyselin; molekulární sekvence - údaje; zastoupení bazí; Base Composition; receptory cytoplazmatické a nukleární; bakteriální proteiny; restrikční enzymy; flagelin; Flagellin; Base Sequence; fylogeneze; Sequence Homology, Nucleic Acid; Anoxybacillus; Bacterial Proteins; DNA Restriction Enzymes